"What have you done?" Accounting for Covid-19 lockdown breaches on talk radio. (October 2022) - Cantarutti, Marina N.; Márquez Reiter, Rosina
Abstract: The establishment of social distancing guidance during the first months of the Covid19 pandemic in the UK made behaviour in public spaces open to scrutiny, as observed in reports of lockdown (non)compliance in different types of media. This paper analyses a collection of 13 calls to BBC phone-ins where people publicly admit to breaking the lockdown. It offers an interactional analysis of the discursive practices with which callers account for their breach and build their moral personas while orienting to the accountability concerns that arise in their interaction with hosts, guest experts, and the participating audience on-air. Callers' accounts were found to be extended objects combining different action components with which they present their licences to breach, list their harm-mitigating strategies, and construct their decisions as informed and common-sensical in the light of the moral dilemmas and disruption that the lockdown introduced to their ordinary lives.